Age and height as determinants of the chemical properties of two morphometrically superior genotypes of Dendrocalamus strictus (Roxb.) Nees: Prospects for advances in industrial applications - Shivani Rohilla; Vikas Rana; Harish S. Ginwal; Unnati Chaudhary; Neeraj Prajapati; Shuank Malik; Santan Barthwal (Advances in Bamboo Science)
Dendrocalamus strictus, commonly known as lathi baans on the Indian subcontinent, holds significant potential as a sustainable raw material for diverse industrial applications, including bioenergy, pulp and paper production, and biodegradable composites. Despite its potential, a comprehensive understanding of its chemical composition, particularly across different growth stages, remains scarce. This gap in knowledge limits its efficient utilization in various industries. Hence, we determined the effect of age and height on the chemical characteristics of two different genotypes of D. strictus. The top part of three-year-old culms was recorded with the highest holocellulose (DS01: 71.9 %, DS02: 72.6 %) and alpha cellulose (DS01: 51.5 %, DS02: 52.8 %) content, while their base showed the highest value of klason lignin (DS01: 26.0 %, DS02: 24.2 %), alcohol-benzene soluble extractives (DS01: 3.3 %, DS02: 2.57 %), and ash content (DS01: 3.93 %, DS02: 4.0 %). The bottom portion of one-year-old culms showed the highest values of cold-water (DS01: 7.02 %, DS02: 7.42 %), hot-water (DS01: 10.6 %, DS02: 11.0 %), and 1 % NaOH solubility (DS01: 26.0 %, DS02: 25.3 %). The effect of age and genotype was significant (p < 0.05) for all chemical characteristics, while the influence of height section was only observed for holocellulose, alpha cellulose and klason lignin content. In contrast to DS01, DS02 exhibited ideal chemical properties for industrial end uses. However, selection of material from an appropriate height in the culm in DS01 may enhance its value for industrial application. These insights are pivotal in determining the ideal harvest age and position, ensuring maximum yield and efficiency in the sustainable utilization of D. strictus resources.